Process optimization of cabinet dried osmotically dehydrated mango (Mangifera indica L. cv. katchamita) slices using response surface methodology - Pagliawan, Elka Mae C.; Rustia, Abigail S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Abstract
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Keywords: Mango -- Philippines